Gluten-free cookies elaborated with buckwheat flour, millet flour and chia seeds - Lara Tatiane Geremias Ferreira BRITES (Food Science and Technology, 2018)
Abstract The aim of this study was to obtain an optimized gluten-free cookie formulation using alternative flours. For this, a 22 central composite rotatable design (CCRD), with varying concentrations of millet flour (MF) and chia seeds (CS), on a base of buckwheat flour (BF), was used. Control cookies were elaborated with 100% wheat flour (WF). The cookies were characterized for texture and other physical tests and by scanning electron microscopy of their internal structure. The response surfaces for the quality parameters of the cookies showed that the higher the proportion of MF used in the formulations, the lower the height and the greater the diameter, expansion factor, and hardness of the cookies. The addition of up to 10% CS showed no influence on the responses. The optimum point was defined as that with diameter, expansion factor, thickness, and hardness closer to the control cookie: 7.5% CS, 40% MF, and 52.5% BF. The substitution of wheat flour by buckwheat flour, millet flour, and chia seeds can be considered a suitable alternative for the preparation of gluten-free cookies.